Positive electrode composition for lithium ion secondary battery, positive electrode for lithium ion secondary battery, and lithium ion secondary battery

By using carbon black with small particle size and long structure and carbon nanotubes with fine fiber diameter as conductive agents in the cathode composition of lithium ion secondary batteries, combined with lithium nickel cobalt manganese composite oxide as active material, the conductive path is solved Insufficient problem was solved, and battery performance with low internal resistance and excellent output characteristics, cycle characteristics and low-temperature characteristics was achieved.

CN111316476BActive Publication Date: 2025-01-24JIANGXI UNIV OF SCI & TECH +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN201880065331.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-09-13
Filing Date
2018-09-28
Publication Date
2025-01-24
Estimated Expiration
2038-09-28

AI Technical Summary

Technical Problem

When existing lithium-ion secondary batteries use carbon black with small particle size and long structure and thick fiber diameter carbon nanotubes, they cannot fully form good conductive paths, resulting in insufficient performance, especially in low temperature environments. Not good.

Method used

Carbon black with small particle size and long structure and carbon nanotubes with fine fiber diameter are used as the conductive agent, combined with lithium nickel cobalt manganese composite oxide as the active material, and the content and proportion of the conductive agent are adjusted to form an excellent conductive path.

Benefits of technology

The internal resistance of the secondary battery of the lithium ion is achieved, the output characteristics, the circulation characteristics, and the low temperature characteristics of the lithium ion are excellent, and the overall performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0002440979360000101
    Figure BDA0002440979360000101
  • Figure BDA0002440979360000111
    Figure BDA0002440979360000111
Patent Text Reader

Abstract

The present invention provides a positive electrode composition for a lithium ion secondary battery that can easily obtain a lithium ion secondary battery with low internal resistance and excellent output characteristics, cycle characteristics, and low temperature characteristics. The positive electrode composition for a lithium ion secondary battery is characterized in that it contains an active material capable of absorbing and releasing lithium ions and a conductive agent, wherein the active material is a lithium nickel cobalt manganese composite oxide, the conductive agent is carbon black and carbon nanotubes, and the BET specific surface area of ​​the carbon black is 100 to 400 m 2 / g, the DBP absorption is 210-380 ml / 100 g, and the average diameter of the carbon nanotubes is 7-15 nm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a positive electrode composition for a lithium ion secondary battery, a positive electrode for a lithium ion secondary battery and a lithium ion secondary battery. Background Art

[0002] As environmental and energy issues become more serious, technology development is becoming more and more popular to realize a low-carbon society that reduces dependence on fossil fuels. Examples of such technology development include the development of low-pollution vehicles such as hybrid electric vehicles and electric vehicles, the development of natural energy power generation such as solar power generation and wind power generation, the development of power storage systems, and the development of next-generation power transmission networks that efficiently supply power and reduce power transmission losses. These technologies are used in many areas.

[0003] One of the key components commonly required in these technologies is a battery. For such a battery, a high energy density is required to miniaturize the system. In addition, a high output characteristic is required to be able to provide a stable power supply without being affected by the ambient temperature of use. Moreover, it is also required to be able to withstand good cycle characteristics of long-term use. Therefore, the replacement of lithium-ion secondary batteries with higher energy density, output characteristics and cycle characteristics from conventional lead-acid batteries, nickel-cadmium batteries, and nickel-hydrogen batteries is being rapidly carried out.

[0004] The basic structure of such lithium-ion secondary batteries is composed of a positive electrode, a negative electrode, a separator, and an electrolyte. The positive electrode is usually composed of a positive electrode composition containing a positive electrode active material such as a lithium composite oxide, a conductive agent, and a binder, and a metal foil current collector such as aluminum. The conductive agent is usually a granular carbon material such as carbon black.

[0005] However, carbon black has a common structure in which nearly spherical primary particles are connected in a bead-like shape, and such a structure is called a structure. The length of the structure is usually evaluated indirectly using the DBP absorption measured in accordance with JIS K6217-4. It is believed that the larger the DBP absorption, the longer the structure and the better the conductivity.

[0006] In recent years, it is required to further improve the energy density and battery performance of the lithium ion secondary battery. Therefore, it is required to further reduce the content of the conductive agent in the electrode as a component that does not contribute to the charge and discharge capacity. Therefore, a technology of using a fibrous carbon material as a conductive agent has been proposed, and the fibrous carbon material has a higher aspect ratio than a granular carbon material such as carbon black, and the conductivity can be improved with a smaller amount.

[0007] Patent Document 1 proposes that carbon nanofibers can form an extremely good conductive path in the electrode by electrically bridging the active material and carbon black, thereby obtaining a battery with excellent cycle characteristics. However, the problem is that when using carbon black, which is believed to improve conductivity with a smaller amount and has a small particle size and a long structure, a good conductive path cannot be fully formed, and sufficient performance cannot be obtained in actual use.

[0008] Patent Document 2 proposes that a battery with excellent output characteristics can be obtained by preventing the conductive agent from being unevenly distributed in the electrode by using carbon black and carbon nanotubes in combination. However, the problem is that since it is assumed that carbon black with a small particle size and a short structure is used, when carbon black with a small particle size and a long structure, which is believed to have better conductivity, is used, the conductive agent is unevenly distributed in the electrode due to aggregation caused by mutual entanglement between the structures, and sufficient performance cannot be obtained in actual use.

[0009] Patent Document 3 proposes that, when the conductive agent as a whole is taken as 100 wt%, by setting the proportion of fibrous carbon material to 1 to 20 wt% and the proportion of granular carbon material to 99 to 80 wt%, the conductivity in the electrode is improved, and a battery with excellent cycle characteristics and output characteristics can be obtained. However, the problem is that, since the proportion of granular carbon material is large, when using carbon black, which is considered to have excellent conductivity and has a small particle size and a long structure, the aggregation caused by the mutual entanglement of the structure makes it impossible to fully form a good conductive path, and sufficient performance cannot be obtained in actual use.

[0010] Patent document 4 proposes that by using carbon black and graphitized carbon fibers together, the conductive path in the positive electrode becomes stable, and a battery with excellent output characteristics and cycle characteristics can be obtained. In addition, Patent document 5 proposes that by using carbon black and fibrous carbon together, a battery with low resistance, excellent discharge capacity and cycle characteristics can be obtained. However, the problem is that in either case, the fiber diameter of the fibrous carbon material is coarse, and a large amount of fibrous carbon material is required to produce a good conductive path. Therefore, it is believed that the proportion of carbon black with excellent liquid retention of the electrolyte is reduced, and the output characteristics when used in a low temperature environment are insufficient in practical use.

[0011] Existing patent literature

[0012] Patent Literature

[0013] Patent Document 1: International Publication No. 2013 / 179909;

[0014] Patent Document 2: Japanese Patent Application Publication No. 2007-80652;

[0015] Patent document 3: Japanese Patent Application Laid-Open No. 11-176446;

[0016] Patent document 4: Japanese Patent Application Publication No. 2001-126733;

[0017] Patent Document 5: Japanese Patent Application Publication No. 2010-238575. Summary of the invention

[0018] Technical issues

[0019] In view of the above problems and circumstances, an object of the present invention is to provide a positive electrode composition for a lithium ion secondary battery that can easily provide a lithium ion secondary battery having a low internal resistance and excellent output characteristics, cycle characteristics, and low-temperature characteristics.

[0020] Solutions to the problem

[0021] As a result of intensive studies, the present inventors have found that the above-mentioned problems can be solved by using carbon black having a small particle size and a long structure or carbon nanotubes having a fine fiber diameter as a conductive agent for a specific active material.

[0022] Specifically, it was discovered that a lithium-ion secondary battery manufactured using a positive electrode composition for a lithium-ion secondary battery comprising a lithium-nickel-cobalt-manganese composite oxide as an active material, carbon black with a small particle size and a long structure as a conductive agent, and carbon nanotubes with a fine fiber diameter has a low internal resistance and excellent output characteristics, cycle characteristics, and low-temperature characteristics, thereby completing the present invention.

[0023] That is, the present invention is specified as follows.

[0024] (1) A positive electrode composition for a lithium ion secondary battery, characterized in that it contains an active material capable of absorbing and releasing lithium ions and a conductive agent,

[0025] The active material is lithium nickel cobalt manganese composite oxide.

[0026] The above-mentioned conductive agent is carbon black and carbon nanotubes.

[0027] The BET specific surface area of ​​the above carbon black is 100 to 400 m 2 / g, DBP absorption is 210~380ml / 100g,

[0028] The average diameter of the carbon nanotubes is 7 to 15 nm.

[0029] (2) The positive electrode composition for lithium ion secondary batteries according to (1) is characterized in that the BET specific surface area of ​​the lithium nickel cobalt manganese composite oxide is 0.20 to 0.55 m 2 / g.

[0030] (3) The positive electrode composition for lithium ion secondary battery described in (1) or (2) is characterized in that the content X (unit: mass %) of the carbon black and the content Y (unit: mass %) of the carbon nanotubes in the positive electrode composition satisfy the following conditions (A) and (B).

[0031] (A) 1.0≤(X+Y)≤3.0;

[0032] (B)0.65≤{X / (X+Y)}≤0.75.

[0033] (4) A positive electrode for a lithium ion secondary battery, comprising the positive electrode composition for a lithium ion secondary battery according to any one of (1) to (3).

[0034] (5) A lithium ion secondary battery comprising the positive electrode for a lithium ion secondary battery according to (4).

[0035] Effects of the Invention

[0036] According to the present invention, a positive electrode composition for a lithium ion secondary battery can be provided, which can easily provide a lithium ion secondary battery having a low internal resistance and excellent output characteristics, cycle characteristics, and low-temperature characteristics. DETAILED DESCRIPTION

[0037] The present invention is described in detail below. The positive electrode composition for lithium ion secondary battery of the present invention is characterized in that it comprises an active material and a conductive agent, wherein the active material is a lithium nickel cobalt manganese composite oxide, the conductive agent is carbon black and carbon nanotubes, and the BET specific surface area of ​​the carbon black is 100 to 400 m 2 / g, the DBP absorption is 210-380 ml / 100 g, and the average diameter of the carbon nanotubes is 7-15 nm.

[0038] The active material in the present invention is a lithium nickel cobalt manganese composite oxide. The lithium nickel cobalt manganese composite oxide is similar to the lithium nickel cobalt manganese composite oxide used as a common battery active material. 0.8 Mn 0.1 Co 0.1 O2、LiNi 0.6 Mn 0.2 Co 0.2 O2、LiNi 0.5 Mn 0.3 Co 0.2 O2、LiNi 0.4 Mn 0.4 Co 0.2 O2、LiNi 1 / 3 Mn 1 / 3 Co 1 / 3O2, etc. Among them, LiNi is preferred because it has an excellent balance of conductivity, capacity, and cycle characteristics. 0.5 Mn 0.3 Co 0.2 O2.

[0039] The BET specific surface area of ​​the lithium nickel cobalt manganese composite oxide in the present invention is preferably 0.20 to 0.55 m 2 / g. By setting the BET specific surface area to 0.20 m 2 / g or more, the number of electrical contacts with the current collector and the conductive agent increases, thereby obtaining sufficient utilization efficiency of the active material. In addition, by setting the BET specific surface area to 0.55 m 2 / g or less, the interaction between particles is suppressed, so that the particles are dispersed more uniformly in the positive electrode composition, and sufficient utilization efficiency of the active material can be obtained.

[0040] The conductive agent in the present invention is carbon black and carbon nanotubes. Carbon black is selected from acetylene black, furnace black, channel black, etc., similar to carbon black commonly used as a conductive agent for batteries. Among them, acetylene black is preferred because of its excellent crystallinity and purity.

[0041] The BET specific surface area of ​​the carbon black in the present invention is 100 to 400 m 2 / g. By setting the BET specific surface area to 100m 2 / g or more, the number of electrical contacts with the active material and the current collector increases, and good electron conductivity can be obtained. In addition, by setting the BET specific surface area to 400m 2 / g or less, the interaction between particles is suppressed, so it is more evenly dispersed in the positive electrode composition, and good conductivity can be obtained. From this perspective, the BET specific surface area of ​​carbon black is preferably 100 to 210 m 2 / g, more preferably 100 to 160 m 2 / g.

[0042] The DBP absorption of the carbon black in the present invention is 210 to 380 ml / 100 g. By setting the DBP absorption to 210 ml / 100 g or more, the structure has sufficient length when used as a conductive agent, and good conductivity can be obtained. In addition, by setting the DBP absorption to 380 ml / 100 g or less, aggregation caused by mutual entanglement between structures can be suppressed, so that it can be more evenly dispersed in the positive electrode composition to obtain good conductivity. From this perspective, the DBP absorption of carbon black is preferably 240 to 280 ml / 100 g.

[0043] The volume resistivity of carbon black in the present invention is not particularly limited, but is preferably lower from the viewpoint of conductivity. Specifically, the volume resistivity measured under 7.5 MPa compression is preferably 0.30 Ω·cm or less, and more preferably 0.25 Ω·cm or less.

[0044] The ash content and water content of the carbon black in the present invention are not particularly limited, but from the perspective of suppressing side reactions, the lower the content, the better. Specifically, the ash content is preferably 0.04% by mass or less, and the water content is preferably 0.10% by mass or less.

[0045] The average diameter of the carbon nanotubes in the present invention is 7 to 15 nm. By setting the average diameter to be greater than 7 nm, aggregation caused by mutual entanglement is suppressed, so that they are more evenly dispersed in the positive electrode composition, and good conductivity can be obtained. In addition, by setting the average diameter to be less than 15 nm, the number of electrical contacts with the active material and the current collector increases, and good electronic conductivity can be obtained. From this perspective, the average diameter of the carbon nanotubes is preferably 7 to 11 nm.

[0046] The carbon black content X (unit: mass %) and the carbon nanotube content Y (unit: mass %) in the present invention are preferably 1.0≤(X+Y)≤3.0 and 0.65≤{X / (X+Y)}≤0.75. By setting it to 1.0≤(X+Y)≤3.0, the content of the conductive agent in the positive electrode composition that is a component that does not contribute to the charge and discharge capacity can be suppressed to a low level, and sufficient conductivity can be maintained. In addition, by setting it to 0.65≤{X / (X+Y)}≤0.75, carbon black and carbon nanotubes form complex bridges in the positive electrode composition, thereby obtaining good conductivity.

[0047] The preparation of the positive electrode composition for lithium ion secondary batteries of the present invention can adopt a known method. For example, it is obtained by mixing a solvent dispersion solution of a positive electrode active material, a conductive agent, and a binder using a ball mill, a sand mill, a twin-screw mixer, a self-rotating revolution mixer, a planetary mixer, a dispersing mixer, etc., and is usually made into a slurry for use. As a positive electrode active material and a conductive agent, the above-mentioned substances can be used. Carbon black and carbon nanotubes can be put into a mixer separately, or can be mixed in advance according to a known method. As a binder, polymers such as polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene copolymer, polyvinyl alcohol, acrylonitrile-butadiene copolymer, and carboxylic acid-modified (meth) acrylate copolymer can be listed. Among them, polyvinylidene fluoride is preferred in terms of oxidation resistance. As a dispersion medium, water, N-methyl-2-pyrrolidone, cyclohexane, butanone, methyl isobutyl ketone, etc. can be listed. When polyvinylidene fluoride is used as a binder, N-methyl-2-pyrrolidone is preferred in terms of solubility.

[0048] In addition, the positive electrode composition for lithium ion secondary battery of the present invention may include components other than positive electrode active material, conductive agent, binder and dispersion medium within the scope of not damaging the effect of the present invention. For example, in order to improve dispersibility, polyvinyl pyrrolidone, polyvinyl imidazole, polyethylene glycol, polyvinyl alcohol, polyvinyl butyral, carboxymethyl cellulose, acetyl cellulose or carboxylic acid modified (meth) acrylate copolymer etc. may be included.

[0049] The positive electrode for lithium ion secondary battery of the present invention is to apply the above slurry on a metal foil current collector such as aluminum, and then remove the solvent contained in the slurry by heating to form a porous body, i.e., an electrode composite layer, in which the positive electrode active material is bonded to the surface of the current collector via a binder. The current collector and the electrode composite layer are further pressed by a roller press to make them close, so as to obtain a target electrode.

[0050] The method for manufacturing the lithium ion secondary battery of the present invention is not particularly limited, and can be carried out by a conventionally known method for manufacturing a secondary battery, for example, it can also be manufactured by the following method. That is, by disposing a polyolefin microporous membrane as an insulating layer between the positive electrode and the negative electrode, and injecting a nonaqueous electrolyte into the gaps between the positive electrode, the negative electrode, and the polyolefin microporous membrane until the nonaqueous electrolyte is fully infiltrated.

[0051] The lithium ion secondary battery of the present invention is not particularly limited, and can be used in a wide range of fields, for example, in portable AV devices such as digital cameras, camcorders, portable audio players, portable LCD TVs, portable information terminals such as notebook personal computers, smart phones, mobile PCs, as well as portable game devices, power tools, electric bicycles, hybrid vehicles, electric vehicles, power storage systems, etc.

[0052] Example

[0053] The positive electrode composition for lithium ion secondary battery of the present invention is described in detail below by way of examples and comparative examples. However, the present invention is not limited to the following examples unless it exceeds the gist of the present invention.

[0054] <Example 1>

[0055] (Positive electrode composition for lithium ion secondary battery)

[0056] The active material prepared had a BET specific surface area of ​​0.48 m 2 / g lithium nickel cobalt manganese composite oxide LiNi 0.5 Mn 0.3 Co 0.2 O2 (manufactured by Jiangxi Jiangte Lithium Battery Material Co., Ltd., "S532"), as a conductive agent, has a BET specific surface area of ​​133 m 2 / g and DBP absorption of 267ml / 100g carbon black (manufactured by Denka, "Li-435"), and an N-methylpyrrolidone solution of carbon nanotubes with an average diameter of 9nm (manufactured by CNano, "LB107"). 96% by mass of the lithium nickel cobalt manganese composite oxide, 1.4% by mass of the carbon black, and 0.60% by mass of the carbon nanotubes were added as a binder and an N-methylpyrrolidone solution of polyvinylidene fluoride as a dispersing medium were mixed to obtain a positive electrode composition for a lithium ion secondary battery.

[0057] (Positive electrode for lithium-ion secondary battery)

[0058] The positive electrode composition for lithium ion secondary batteries was applied onto an aluminum foil having a thickness of 20 μm using a baking coater and dried, and then pressed and cut to obtain a positive electrode for lithium ion secondary batteries.

[0059] (Negative electrode for lithium-ion secondary battery)

[0060] A negative electrode composition for a lithium-ion secondary battery [95% by mass of graphite (manufactured by Shenzhen Bettery Co., Ltd., "AGP-2A"), 1.0% of carbon black (manufactured by Denka, "Li-400"), 1.5% of polyvinylidene fluoride, and 2.5% of styrene-butadiene copolymer] was applied to a copper foil with a thickness of 20 μm using a baking coater and dried. The foil was then pressed and cut to obtain a negative electrode for a lithium-ion secondary battery.

[0061] (Lithium-ion secondary battery)

[0062] The positive electrode, separator (manufactured by LLC, "Celgard"), and negative electrode were stacked and laminated together, packaged and pre-sealed with an aluminum laminate film, and then injected with an electrolyte, formatted, and vacuum-sealed to obtain a laminated lithium-ion secondary battery.

[0063] [Internal resistance]

[0064] The manufactured lithium ion secondary battery was charged / discharged for 5 cycles within a voltage range of 2.75 to 4.2 V, and then impedance analysis was performed within a frequency range of 10 MHz to 0.001 Hz and a vibration voltage of 5 mV. The internal resistance of this example was 37.5 mΩ.

[0065] [Output characteristics (capacity retention rate at 3C discharge)]

[0066] The produced lithium ion secondary battery was charged at 4.2V and 0.2C at 25°C with constant current and constant voltage, and then discharged at a constant current of 0.2C until 2.75V. Then, the discharge current was changed to 0.2C and 3C, and the discharge capacity relative to each discharge current was measured. Then, the capacity retention rate at 3C discharge relative to 0.2C discharge was calculated. The capacity retention rate at 3C discharge in this embodiment was 96.5%.

[0067] [Cycle characteristics (cycle capacity retention rate)]

[0068] The prepared lithium ion battery was charged at 4.2V and 1C constant current and constant voltage at 25°C, and then discharged at 6C constant current until 2.75V. The charging and discharging cycles were repeated, and the ratio of the discharge capacity of the 800th cycle to the discharge capacity of the first cycle was calculated as the cycle capacity retention rate. The cycle capacity retention rate of this example was 84.0%.

[0069] [Low-temperature output characteristics (capacity retention rate when discharging at -20°C)]

[0070] The prepared lithium ion secondary battery was charged at 4.2V and 0.2C at 25°C with constant current and constant voltage, and then discharged at a constant current of 1C until 2.75V. Then, it was charged at 4.2V and 0.2C at -20°C with constant current and constant voltage, and then discharged at a constant current of 1C until 2.75V. Then, the capacity retention rate at -20°C relative to the discharge at 25°C was calculated. The capacity retention rate at -20°C discharge in this embodiment is 63.9%.

[0071] <Example 2>

[0072] A positive electrode composition for a lithium ion secondary battery, a positive electrode for a lithium ion secondary battery, and a lithium ion secondary battery were prepared in the same manner as in Example 1 except that the content of carbon black was changed to 1.2 mass % and the content of carbon nanotubes was changed to 0.80 mass %, and various evaluations were performed. The results are shown in Table 1.

[0073] <Example 3>

[0074] A positive electrode composition for a lithium ion secondary battery, a positive electrode for a lithium ion secondary battery, and a lithium ion secondary battery were prepared in the same manner as in Example 1 except that the content of carbon black in Example 1 was changed to 1.6 mass % and the content of carbon nanotubes was changed to 0.40 mass %, and various evaluations were performed. The results are shown in Table 1.

[0075] <Example 4>

[0076] A positive electrode composition for a lithium ion secondary battery, a positive electrode for a lithium ion secondary battery, and a lithium ion secondary battery were prepared in the same manner as in Example 1 except that the content of carbon black in Example 1 was changed to 0.63 mass % and the content of carbon nanotubes was changed to 0.27 mass %, and various evaluations were performed. The results are shown in Table 1.

[0077] <Example 5>

[0078] A positive electrode composition for a lithium ion secondary battery, a positive electrode for a lithium ion secondary battery, and a lithium ion secondary battery were prepared in the same manner as in Example 1 except that the content of carbon black in Example 1 was changed to 2.2 mass % and the content of carbon nanotubes was changed to 0.93 mass %, and various evaluations were performed. The results are shown in Table 1.

[0079] <Example 6>

[0080] In addition to changing the lithium nickel cobalt manganese composite oxide of Example 1 to a BET specific surface area of ​​0.15 m 2 / g lithium nickel cobalt manganese composite oxide LiNi 0.5 Mn 0.3 Co 0.2 O2 (L532 manufactured by Jiangxi Jiangte Lithium Battery Material Co., Ltd.), a positive electrode composition for lithium ion secondary battery, a positive electrode for lithium ion secondary battery and a lithium ion secondary battery were prepared in the same manner as in Example 1, and various evaluations were performed. The results are shown in Table 1.

[0081] <Example 7>

[0082] In addition to changing the lithium nickel cobalt manganese composite oxide of Example 1 to a BET specific surface area of ​​0.15 m 2 / g lithium nickel cobalt manganese composite oxide LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2 (L333 manufactured by Jiangxi Jiangte Lithium Battery Material Co., Ltd.), a positive electrode composition for lithium ion secondary battery, a positive electrode for lithium ion secondary battery and a lithium ion secondary battery were prepared in the same manner as in Example 1, and various evaluations were performed. The results are shown in Table 1.

[0083] <Example 8>

[0084] In addition to changing the carbon black of Example 1 to a carbon black having a BET specific surface area of ​​382 m 2 A positive electrode composition for a lithium ion secondary battery, a positive electrode for a lithium ion secondary battery, and a lithium ion secondary battery were prepared in the same manner as in Example 1, except that carbon black having a DBP absorption of 305 ml / 100 g (manufactured by Denka) was used, and various evaluations were performed. The results are shown in Table 1.

[0085] <Comparative Example 1>

[0086] A positive electrode composition for a lithium ion secondary battery, a positive electrode for a lithium ion secondary battery, and a lithium ion secondary battery were prepared in the same manner as in Example 1 except that the content of carbon black in Example 1 was changed to 0 mass % and the content of carbon nanotubes was changed to 2.0 mass %, and various evaluations were performed. The results are shown in Table 2.

[0087] <Comparative Example 2>

[0088] A positive electrode composition for a lithium ion secondary battery, a positive electrode for a lithium ion secondary battery, and a lithium ion secondary battery were prepared in the same manner as in Example 1 except that the content of carbon black in Example 1 was changed to 2.0 mass % and the content of carbon nanotubes was changed to 0 mass %, and various evaluations were performed. The results are shown in Table 2.

[0089] <Comparative Example 3>

[0090] In addition to changing the carbon black of Example 1 to a carbon black having a BET specific surface area of ​​58 m 2 A positive electrode composition for a lithium ion secondary battery, a positive electrode for a lithium ion secondary battery, and a lithium ion secondary battery were prepared in the same manner as in Example 1, except that carbon black (manufactured by Denka Co., Ltd., “Li-250”) with a DBP absorption of 200 ml / 100 g was used, and various evaluations were performed. The results are shown in Table 2.

[0091] <Comparative Example 4>

[0092] In addition to changing the carbon black of Example 1 to a carbon black having a BET specific surface area of ​​877 m 2 A positive electrode composition for a lithium ion secondary battery, a positive electrode for a lithium ion secondary battery, and a lithium ion secondary battery were prepared in the same manner as in Example 1, except that carbon black (manufactured by Lion) with a DBP absorption of 390 ml / 100 g was used, and various evaluations were performed. The results are shown in Table 2.

[0093] <Comparative Example 5>

[0094] A positive electrode composition for a lithium ion secondary battery, a positive electrode for a lithium ion secondary battery, and a lithium ion secondary battery were prepared in the same manner as in Example 1 except that the carbon nanotubes in Example 1 were replaced with carbon nanotubes having an average diameter of 5 nm (manufactured by WAKO CHEMICAL), and various evaluations were performed. The results are shown in Table 2.

[0095] <Comparative Example 6>

[0096] A positive electrode composition for a lithium ion secondary battery, a positive electrode for a lithium ion secondary battery, and a lithium ion secondary battery were prepared in the same manner as in Example 1 except that the carbon nanotubes in Example 1 were replaced with carbon nanotubes having an average diameter of 25 nm (manufactured by WAKO CHEMICAL), and various evaluations were performed. The results are shown in Table 2.

[0097] <Comparative Example 7>

[0098] A positive electrode composition for a lithium ion secondary battery, a positive electrode for a lithium ion secondary battery, and a lithium ion secondary battery were prepared in the same manner as in Example 1 except that the carbon nanotubes in Example 1 were replaced with vapor-grown carbon fibers having an average diameter of 150 nm, and various evaluations were performed. The results are shown in Table 2.

[0099] Table 1

[0100]

[0101] Table 2

[0102]

[0103] From the results in Tables 1 and 2, it is understood that the lithium ion secondary battery produced using the positive electrode composition for lithium ion secondary batteries of the present invention has a small internal resistance and is excellent in output characteristics, cycle characteristics, and low-temperature characteristics.

Claims

1. A positive electrode composition for a lithium ion secondary battery, characterized in that Contains active materials and conductive agents that can absorb and release lithium ions. The active material is lithium nickel cobalt manganese composite oxide, The conductive agent is carbon black and carbon nanotubes. The BET specific surface area of ​​the carbon black is 133 to 400 m 2 / g, the DBP absorption is 240-380ml / 100g, and the average diameter of the carbon nanotubes is 7-15nm.

2. The positive electrode composition for lithium ion secondary battery according to claim 1, characterized in that The BET specific surface area of ​​the lithium nickel cobalt manganese composite oxide is 0.20 to 0.55 m 2 / g.

3. The positive electrode composition for lithium ion secondary battery according to claim 1 or 2, characterized in that: The carbon black content X and the carbon nanotube content Y in the positive electrode composition satisfy the following conditions (A) and (B), and the units of X and Y are both mass %: (A) 1.0≤(X+Y)≤3.0; (B)0.65≤{X / (X+Y)}≤0.

75.

4. A positive electrode for a lithium ion secondary battery, wherein: A positive electrode composition for a lithium ion secondary battery comprising the positive electrode composition according to any one of claims 1 to 3.

5. A lithium ion secondary battery, wherein: A positive electrode for a lithium ion secondary battery according to claim 4 is provided.

Citation Information

Patent Citations

  • Lithium secondary battery

    JP1999176446A

  • Nonaqueous electrolytic material

    JP2001126733A

  • Slurry for forming lithium ion battery electrode and lithium ion battery

    JP2007080652A

  • Electrode for lithium ion battery and its manufacturing method

    JP2010238575A

  • Electrode for lithium ion secondary cell, method for preparing paste for said electrode and method for manufacturing said electrode

    WO2013179909A1